Choices in healing : integrating the best of conventional and complementary approaches to cancer - Lerner, Michael, 1943 October 22- (MIT Press, 1994)
A comprehensive guide for cancer patient or health professional who seeks a comprehensive overview of the available choices, both treatments and in living with cancer. Detailed explanations and evalutions of a wide range of complementary therapy programs, including spiritual and psychological approaches, nutritional therapies, physical therapies, pharmacological therapies, and traditional medicines.